Implementation of Guided Inquiry Learning Model in Improving Students' Understanding of Paraphrasing (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Improving the quality of student writing through guided inquiry-based paraphrasing activities, where students are actively involved in the learning process and encouraged to gain a deeper understanding of the topic being studied. The holistic guided inquiry approach can provide benefits in improving students' paraphrasing skills by placing them as active subjects in the learning process. The method used in this study is based on the syntax of the guided inquiry learning model, which was implemented on 30 senior students in the geography education program Pattimura University. The study was then evaluated to determine the significance and impact of the implementation process towards the research objective of improving student writing quality through paraphrasing skills. The results showed that the improvement in students' skills by applying the guided inquiry model had a significant impact, as seen from the evaluation results of the pre-test and post-test. Furthermore, after conducting significance testing through the Wilcoxon test, the asymp. Sig. (2-tailed) value was 0.000, which means that the value is less than 0.05. This indicates a significant improvement in students' paraphrasing understanding through the guided inquiry method, and it was effective in being implemented by 80% of the students.